Study on the Effectiveness of One Stop Integrated Services (PTSP) in Business Licensing in Bandung City - Heriyanto, Dedi; Ardiyanti, Ardiyanti; Alam, Kurniawati (Journal Social Civilecial, 2023)
This paper focuses on assessing the efficiency of PTSP in enabling business permit in Bandung City of Indonesia. PTSP is the government’s program that it has launched to simplify various bureaucratic procedures and increase the transparency of governance to unleash the economic potential of a country. Employing a survey questionnaire, quantitative data was obtained from 200 business owners and government officials who deal with PTSP concerning factors such as time taken to process licenses, the level of transparency and user satisfaction. The findings have revealed that PTSP has led to the cutting down of processing time, enhance the level of opacity and has received accolades by the business fraternity. However, there are also problems to face such as inadequate organizational infrastructure and reluctance for change. Consequently, the study enhances the existing literature by presenting a quantitative analysis on PTSP impact assessment in an urban context as well as presenting guidelines on how to address the emerging challenges that continue to emanate on the efficiency of the system.